Churn flow in high viscosity oils and large diameter columns - Mohammed, Shara K.; Hasan, Abbas; Dimitrakis, Georgios; Azzopardi, Barry J. (Elsevier, 2018)
Churn flow is an important intermediate flow regimoccurring in between slug and annular flow patterns in two-phase flow, with profound implications in chemical and petroleum industry. The majority of studies to date in churn flow has been carried out mainly using water or liquids of low viscosities and limited information exists regarding the behaviour of high viscosity liquids which resemble realistic process conditions. In this paper, a study that investigated churn flow and its characteristics in high viscosity oils (360 and 330 Pa.s) and large diameter columns (240 and 290mm) is presented for a first time. Transition to churn flow regime starts when the structure velocity, length and frequency of the liquid bridges, which appear at the end of slug flow, increase. In churn flow, gas flows at the core of the oil column with a wavy passage, leaving the top surface open to atmosphere with a possibility of creating a very long bubble. The average length of the bubbles seen to decrease with increasing the gas flow rate. While, no considerable change is observed in void fraction, structure velocity and film thickness at this flow pattern.